CM NCTF With Velocity Feedforward Controller Design For Tracking Control Of An AC Driven X-Y Ball Screw Mechanism - Hasim, Norhaslinda (Springer Nature Singapore Pte. Ltd., 2017)
This paper presents an improved practical controller for enhancing the tracking performance of a ball screw mechanism. Essentially, a controller with practical and easy to design has been preferred for high motion control performance. The existing continuous motion nominal characteristic trajectory following (CM NCTF) controller demonstrates a low accuracy achievement at high frequency motion,where at 5 Hz, the percentage of error are higher than 10% and 15% for amplitude of 1 mm and 10 mm respectively. The NCTF controller comprises of a nominal characteristic trajectory (NCT) and a PI compensator where the controller parameters are easily determined and it is free from exact modeling.In this paper, the CM NCTF controller with velocity feedforward compensator has been proposed in order to enhance the tracking motion accuracy. The simulation results shown that the CM NCTF controller with velocity feedforward compensator achieves better tracking performances than that the CM NCTF controller alone by showing more than three times smaller motion error.